Advanced Encryption Standard Mobile Application to Improve College Entrance Security in UNIMAS - Azlina, Ahmadi Julaihi; Ping Ping, Tan; Fateen Afeefa, Md Nor (2022)
Rafflesia College is one of the colleges in UNIMAS located outside of campus in Desa Ilmu, Kota Samarahan. Currently, the college does not have a clear log for visitors who enter and leave the college. There is also the chance that the visitor will enter the college using a fake identity. This paper implements improved entrance security with the Advanced Encryption Standard (AES) algorithm. In addition, this solution also ensures the confidentiality of the visitors’ data. This system has three users which are administrators, students, and security officers. This enhanced entrance security allows the students to put in a request for the visitor by giving the visitor’s to the security officer for approval. This proposed system is an Android-based application developed using the Waterfall methodology. This application also tracks the entrance and leave time of the visitors. A questionnaire was conducted during the process and about 95% of the respondents find the application improves the security of the entrance.